Expert evaluation of the labor competencies of the Specialization Program in Respiratory Therapy in Critical Care in Bogotá. - Ausique Pedroza, Luz Adriana
The Specialization in Respiratory Therapy in Critical Care is defined as a postgraduate degree in the health area with scientific and humanistic training; that tends for the formation of the student in the evaluation, treatment and rehabilitation of the patients in critical condition, with cardiorespiratory alteration of base or secondary to multisystemic damage. Therefore, the objective of this project was: To evaluate with experts the labor competencies of the specialization program in respiratory therapy in critical care in Bogotá. For which a descriptive, cross-sectional design with an analytical approach was used, where categories of evaluation of relevance, relevance and sufficiency were defined, using a Likert-type scale, 10 experts in Intensive Care were selected to evaluate each competence. Subsequently, a statistical analysis was carried out to show the agreement between the experts. Within the results, it can be seen that between 90 and 80% of the experts rated the competencies between the moderate and high levels. The foregoing supports the quality of education offered to students of the specialization and how it meets the needs of the service-providing institutions and the country.